The potential of unused small-scale water reservoirs for climate change adaptation: A model- and scenario based analysis of a local water reservoir system in Thuringia, Germany - Heinzel, Christine; Fink, Manfred; Höllermann, Britta (Frontiers in Water, 2022)
The 6th Intergovernmental Panel on Climate Change (IPCC) report (2021) stated that hot extremes have become more frequent and intense across most land regions in the past decades. It is projected that the changing climatic conditions in Germany and Thuringia in particular will lead to a higher frequency of drought events. Thus, it is vital to develop local adaptation strategies to mitigate the effects of droughts on agriculture to ensure future crop production. Water resource infrastructure has a critical role in planning future climate change adaptation measures that are sustainable. As the construction of new dams and reservoirs is controversial, it is preferable to use existing infrastructures, if they are suitable. Small-scale water management reservoirs built in Thuringia during the GDR (German Democratic Republic) and decommissioned after the German reunification were examined in this study to determine whether their reuse could be considered as a potential adaptation strategy. For this purpose, three reservoirs in Thuringia were selected. The impact of climate change on soil moisture, water availability and crop production, and the use of water from the reservoirs to meet future irrigation needs were modeled using the Water Evaluation and Planning system (WEAP). The modeled climatic changes have direct effects on the soil moisture status, leading to a higher water demand of the local agriculture. The results show that the crop water needs could double between near future (2020-2040) and distant future (2071-2100). However, predicted declines in yields can be mitigated by irrigation; modeling results indicate that supplemental irrigation with reservoir water mitigates projected losses and even allows 6.2 % to 13.5 % more crop production. Hence, the reuse of the reservoirs is worth to be considered as an adaptation strategy by policymakers. In addition to a cost-benefit analysis for future evaluation of the reservoirs, local user interests and demands need to be included avoiding conflicts about water. In general, WEAP as a modeling tool and the findings of the study show, that this research approach could be used to investigate the potential adaptive capacity of other small-scale water infrastructures.